Synthesis of N-sulfenyl-sulfoximines and -sulfenamides through a metal-free N–H/S–H dehydrocoupling reaction. Issue 1 (25th September 2017) - Yang, Lu; Feng, Jie; Qiao, Mei; Zeng, Qingle
Abstract : A metal-free, iodine-catalyzed N–H/S–H dehydrocoupling reaction of sulfoximines and anilines with various thiols to construct sulfur–nitrogen bonds has been developed. Abstract : A metal-free, iodine-catalyzed N–H/S–H dehydrocoupling reaction of sulfoximines and anilines with various thiols to construct sulfur–nitrogen bonds is herein presented. A variety of structurally diverse N -sulfenylsulfoximines and sulfenamides were prepared with up to 97% yield. The reaction was carried out in the presence of hydrogen peroxide in PEG400 under mild conditions.